Triagem neonatal em Minas Gerais: análise do contexto histórico e político-institucional com enfoque nas estratégias empregadas e resultados alcançados - Jose Nelio Januario (2015)
Newborn screening (NBS) is a set of procedures and practices in public health, which presents relatively new features in the traditional health system context. It is currently established in almost all continents. NBS outcomes are recognized as relevant at an international level. The Newborn Screening Program of Minas Gerais State (NBSP-MG), Brazil, has reached the large number of five million children submitted to the newborn screening tests since 1993 when it was launched. The present study shows the actions developed by the NBSP-MG, considering historical issues and, at the same time, the international development of the NBS methods and strategies. The NBSP-MG development is closely associated with the creation of the Center for Newborn Screening and Genetic Diagnostics from the Faculty of Medicine, Federal University of Minas Gerais (Nupad). Nupad assumes the technical coordination of the NBSP-MG. The NBSP-MG was implemented by the State Health Administration of Minas Gerais in partnership with Nupad. In addition to the screening procedures, the Center has been engaged in educational and outreach programs. Nupad has extended its activities to the molecular area, in order to support the diagnosis after the screening tests. As part of the outcomes of this thesis, four articles illustrate the diversity of methodologies used in NBS and its challenges. The article Congenital toxoplasmosis in the state of Minas Gerais, Brazil: a neglected infectious disease, published in 2014, illustrates the expansion of newborn screening procedures into other public health such as women's health. A pilot study performed in 2008 detected an incidence of 1.3 / 1000 for congenital toxoplasmosis in the state of Minas Gerais. That finding strengthened the initiatives to establish the current Surveillance Program for Congenital Toxoplasmosis in Minas Gerais. The article High incidence of partial biotinidase deficiency from a pilot newborn screening study in Minas Gerais, Brazil, published in the Journal of Inherited Metabolic Disease, illustrates some difficulties to be overcome to establish an appropriate phenotype-genotype correlation in some inherited metabolic diseases. The results showed a high incidence of partial deficiency of biotinidase (1 / 26,127) compared to studies in other countries. The performed genetic studies demonstrate the solid experience obtained by Nupad with molecular test analysis. The manuscript Neonatal screening for cystic fibrosis in Minas Gerais, Brazil: Screening results of 2.5 million newborns over a 10-year study period discusses current worldwide strategies for NBS using immunoreactive trypsin (IRT) marker that is known to have limited sensitivity and specificity for the detection of cystic fibrosis (CF). Together with the sweat test NBSP-MG protocol reached a sensitivity rate of 89.6% and a positive predictive value of 99.0%. The false-negative rate was 10.6% (24 cases). The incidence of CF was 1/10,657 in a universe of 2,461,685 newborns screened during 10 years. The article Sickle Cell Disease in Minas Gerais, Brazil: the experience in 16 years of newborn screening (2015) shows consistent epidemiological data in the state of Minas Gerais for sickle cell disease and other hemoglobinophaties. The incidence of the sickle cell disease (SS, SC, SD, SBeta thalassemia) was 1:1.400 newborns. The article aims at discussing novel methods to control efficiently the NBS short follow-up until the first consultation of the baby. In addition to the results showed in the articles, the thesis present other results and analyses on the technical and organizational field that contributed decisively to support the goal of this study. The results highlight the impact generated by the actions of the NBSP-MG upon children who were born with several congenital and hereditary conditions. Such individuals are at high risk of morbimortality if not detected during newborn screening. The actions of the NBSP-MG occur at all levels of the Brazilian Universal Health System (SUS) organization. The diagnosis and care network organized throughout the state during the 22 years of the NBSP-MG is currently ready to include further potentially harmful diseases that are possible to detect in newborns and in other age groups.